Practicing Nostalgia: Time and Memory in Nabokov's Early Russian Fiction - Philip Sicker (Studies in 20th & 21st Century Literature, 1987)
Nabokov's earliest Russian fiction reveals his lifelong preoccupation with time and his complex strategies for preserving heightened moments of experience. Dissatisfied with the brevity of involuntary (Proustian) recall, his émigré protagonists strive to inhabit their Russian past more fully through a painstaking process of aesthetic re-creation. Beginning with a handful of vivid recollections, the hero of Mary gradually fabricates a past that is more intensely real than the original. Nabokov's most mature characters, however, recognize the solipsistic danger and utility of living in a vanished mental paradise. Turning to the present, they find unexpected beauty in the arrangement of ordinary objects in Berlin. In order both to intensify these perceptions and to memorialize them, the heroes of "Torpid Smoke" and "A Guide to Berlin" adopt a remarkable strategy: projecting themselves into an imagined future, they view the scene before them as if it were already a memory. This ocular adjustment endows the perceived objects with a radiance, fixity, and "relief" that they would acquire (and lose) only in a moment of extraordinary recall; but this act simultaneously preserves the impression indelibly when it becomes part of the actual past. In short, by anticipating and accelerating time's destructive movement, by "practicing nostalgia" for the past while it is yet present, these individuals arrest the process of forgetting.
Keywords: time; memory; nostalgia; Nabokov; Russian fiction; Proustian; émigré protagonist; aesthetics; re-creation; Torpid Smoke; A Guide to Berlin; future; past; forgetting